An Assessment of Water and Sediment Quality of River in India with Special Reference to Pesticide Contamination, a Case Study - A.H, Divya; A. Soloman, P (International Journal of Engineering and Technology, 2018)
Drinking water quality has become a serious issue in many countries due to the scarcity of fresh water resources. Water quality monitoring is the first step for the management and conservation of aquatic system. The contamination of OrganoChlorine Pesticides (OCPs) is very harmful for the environment and human beings. The presence of OCPs in surface water and in the bottom sediment in the Chalakudy River was investigated to evaluate the pollution load and distribution level of OCP seasonally over a period of 3 years from January 2013 to December 2015. Surface water sample and bottom sediment were collected from nine different sites (upstream, midstream and downstream) and analyzed for their profile of important physicochemical parameters and for persistence of OCP. To know the present trends in the river clearly ,temporalÂ distributionÂ and spatial distribution of OCPs and other parameters are studied based on three season(winter, summer, and monsoon).Obtained trend in eachÂ yearÂ were comparedÂ through sampling and analysis.Â Â Â